Analisis Faktor Berhubungan dengan Penatalaksanaan Protokol Kesehatan Dalam Pencegahan Penularan Covid-19 di Wilayah Kerja Puskesmas Lapai Kecamatan Ngapa Kabupaten Kolaka Utara - Besse Intang; Rahmawati Azis; Andi Yusuf (NERSMID : Jurnal Keperawatan dan Kebidanan, 2022)
Covid-19 disease is an infectious disease caused by severe acute respiratory syndrome coronavirus 2. The total number of positive Covid-19 patients worldwide has reached 41,959,864 confirmed cases with 1,142,073 deaths worldwide. The purpose of the study was to analyze factors related to the management of health protocols in preventing the transmission of covid-19 in the Lapai Health Center Work Area, Ngapa District, North Kolaka Regency. The type of research used is descriptive analytic with a cross-sectional study approach, where all observed variables are measured simultaneously when the research takes place. The results showed that there was no relationship between gender, occupation and the management of health protocols in preventing transmission of covid-19 and that there was a relationship between age, education, knowledge and attitudes with the management of health protocols in preventing transmission of covid-19, while knowledge was the dominant factor related to management. health protocol in preventing the transmission of covid-19 in the working area of the Lapai Public Health Center, Ngapa District, North Kolaka Regency in 2021. Suggestions in the research are that it can contribute to the Lapai Health Center to design health programs in order to reduce the number of cases and death rates due to Covid-19, can broaden insight and knowledge about covid-19 and how to do proper prevention and can encourage further research with a different approach and can be an additional reference for reading in the library and can increase knowledge for readers ca, especially in the effort to manage health protocols in preventing the transmission of COVID-19